Academic Challenges for Chinese Transfer Students in Engineering - O'Connell, Robert M; Resuli, Nuerzati (Journal of International Students, 2020)
This article describes a research study determining the most significant academic challenges experienced by Chinese transfer students in engineering at an American university. The survey-based study examined eight areas where transfer students may have academic difficulty and determined that the most significant of those concern transfer credit issues, student–instructor and student–student language difficulties, and classroom culture differences. The cultural differences, related to course syllabi, classroom discussion and group work, and frequency of assignments and exams, are partially explained in terms of a theoretical framework based on Hofstede’s power distance and risk avoidance elements. Recommendations are made of ways to ease these challenges and make the intercultural experience richer for both the transfer students and their American hosts.